Split-hand/split-foot malformation (SHFM) - Mondal, Monojit; Rana, Kriti Sundar; Banerji, Nayan; Bose, Sayan; Biswas, Tanmoy; Biswas, Biswajit; Mandal, Pijush Kanti (Asian Journal of Medical Sciences, 2014)
Split-hand/split-foot malformation (SHFM), also known as ectrodactyly or lobster claw hand is a congenital limb malformation, characterized by a deep median cleft of the hand and/or foot due to the absence of the central rays of the autopod. It may occur singly or in association with syndromes, former being mostly autosomal dominant but autosomal recessive variety is rare. We are reporting a case of ectrodactyly with autosomal recessive mode of inheritance DOI: http://dx.doi.org/10.3126/ajms.v6i1.10018 Asian Journal of Medical Sciences Vol.6(1) 2015 122-123